Acute Cardiovascular Effects of Hydrotreated Vegetable Oil Exhaust - Marc-Derrien, Youna; Gren, Louise; Dierschke, Katrin; Albin, Maria; Gudmundsson, Anders; Wierzbicka, Aneta; Sandberg, Frida (Frontiers in Physiology, 2022)
Ambient air pollution is recognized as a key risk factor for cardiovascular morbidity and mortality contributing to the global disease burden. The use of renewable diesel fuels, such as hydrotreated vegetable oil (HVO), have increased in recent years and its impact on human health are not completely known. The present study investigated changes in cardiovascular tone in response to exposure to diluted HVO exhaust. The study participants, 19 healthy volunteers, were exposed in a chamber on four separate occasions for 3 hours and in a randomized order to: 1) HVO exhaust from a wheel loader without exhaust aftertreatment, 2) HVO exhaust from a wheel loader with an aftertreatment system, 3) clean air enriched with dry NaCl salt particles, and 4) clean air. Synchronized electrocardiogram (ECG) and photoplethysmogram (PPG) signals were recorded throughout the exposure sessions. Pulse decomposition analysis (PDA) was applied to characterize PPG pulse morphology, and heart rate variability (HRV) indexes as well as pulse transit time (PTT) indexes were computed. Relative changes of PDA features, HRV features and PTT features at one, two, and three hours after onset of the exposure was obtained for each participant and exposure session. The PDA index A13, reflecting vascular compliance, increased significantly in both HVO exposure sessions but not in the clean air or NaCl exposure sessions. However, the individual variation was large and the differences between exposure sessions were not statistically significant.